ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PIUTANG TAK TERTAGIH PADA PT. KAWASAN INDUSTRI MEDAN (PERSERO) DENGAN MOTIVASI MEMBAYAR SEBAGAI VARIABEL MODERATING - Endang Budiwati Sinaga; John Gilbert Lumbanraja (JURNAL MANAJEMEN, 2019)
The objective of this study was to analyze the influence of customer satisfation, collectability, the stability of customer sales, and the pay motivation as the moderating variable on doubtful account receivable of PT. Kawasan Industri Medan (Persero). The study used causal research method. The population in the study is the tenants that located in Kawasan Industri Medan (Medan Industrial Park) and some of them were used as the samples. Primary data were gathered by using questionares. Hypothesis was tested by using multiple linear regression analysis and residual test with an SPSS software program. The result of the study showed that customer satisfation, collectibility, and the stability of customer sales had significant influence on doubtful account receivable simultaneously. Partially, customer satisfation, and the stability of customer sales had positif significant influence on doubtful account receivable. Pay motivation as the moderating variable moderates the correlation of customer satisfaction, collectability, stability of customer sales with doubtful account receivable on PT. Kawasan Industri Medan (Persero).